Integrating species life-history traits and patterns of deforestation in amphibian conservation planning - Becker, C. G.; Loyola, R. D.; Haddad, Celio Fernando Baptista [UNESP]; Zamudio, K. R. (Wiley-Blackwell Publishing, Inc, 2010)
Aim To identify priority areas for amphibian conservation in southeastern Brazil, by integrating species life-history traits and patterns of deforestation.Location State of São Paulo, Brazil.Methods We used the software Marxan to evaluate different scenarios of amphibian conservation planning. Our approach differs from previous methods by explicitly including two different landscape metrics; habitat split for species with aquatic larvae, and habitat loss for species with terrestrial development. We evaluated the effect of habitat requirements by classifying species breeding habitats in five categories (flowing water, still water permanent, still water temporary, bromeliad or bamboo, and terrestrial). We performed analyses using two scales, grid cells and watersheds and also considered nature preserves as protected areas.Results We found contrasting patterns of deforestation between coastal and inland regions. Seventy-six grid cells and 14 watersheds are capable of representing each species at least once. When accounting for grid cells already protected in state and national parks and considering species habitat requirements we found 16 high-priority grid cells for species with one or two reproductive habitats, and only one cell representing species with four habitat requirements. Key areas for the conservation of species breeding in flowing and permanent still waters are concentrated in southern state, while those for amphibians breeding in temporary ponds are concentrated in central to eastern zones. Eastern highland zones are key areas for preserving species breeding terrestrially by direct or indirect development. Species breeding in bromeliads and bamboos are already well represented in protected areas.Main conclusions Our results emphasize the need to integrate information on landscape configuration and species life-history traits to produce more ecologically relevant conservation strategies.
Keywords: Amphibian declines; area prioritization; Brazil; habitat fragmentation; habitat split; protected areas; systematic conservation planning